Assessment and Treatment of Patients with Comorbidity of Mental Health Problems and Alcohol Use Disorders: Experiences of Clinicians and Patients in the UK and Poland. (16th April 2019) - Klingemann, Justyna; Welbel, Marta; Nicaise, Pablo; Priebe, Stefan; Matanov, Aleksandra; Bird, Victoria; Moskalewicz, Jacek
Abstract: Aims: Treatment of patients with comorbidity of mental health problems and alcohol use disorder (AUD) constitutes a challenge in many countries. The article aimed at exploration of personal experiences of clinicians and patients with the comorbidity regarding its assessment, treatment and organization of care in Poland and the UK. Methods: Data were collected via in-depth, semi-structured interviews with clinicians ( N = 28) and patients ( N = 81) in both countries, according to a unified study protocol. Maximum variation sampling was applied to both study groups. All interviews' transcripts were coded (CAQDA) and the consistency of coding across centres was assessed. Data analysis was performed according to the principles of thematic analysis. Results: Our data show that most patients with AUD admitted at the psychiatric wards—apart from assessment which is a standard procedure during admission—receive only minimal support during their hospital stay. This is the consequence of two factors: lack of trained staff prepared to help those patients and a priority given to self-referrals by AUD units. At the same time, it is recognized by clinicians and patients that more support is needed to encourage the utilization of AUD services and to prevent the drop-out. Conclusions: In order to improve the system response, the use of screening instruments in the process of the assessment of AUD and establishment of special procedures supporting motivation and adherence to treatment and preventing drop-out merits consideration. Moreover, the psychiatric wards and the AUD services could possibly profit from formalization of the collaboration between services.